2014
DOI: 10.1002/chp.21255
|View full text |Cite
|
Sign up to set email alerts
|

Not Enough Time or a Low Priority? Barriers to Evidence-Based Practice for Allied Health Clinicians

Abstract: Achieving higher uptake of EBP among allied health clinicians requires a cultural shift, placing higher value on these activities despite the challenging context of constant pressures to increase patient flow. Addressing EBP through small group projects rather than considering it to be an individual responsibility may be more acceptable to both clinicians and managers, with added benefits of peer support for both evaluating evidence and translation into practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 16 publications
5
83
0
4
Order By: Relevance
“…However, the literature abounds with studies that indicate this type of practice is far from reality. Findings from research have indicated that, although health professionals from a variety of disciplines believe in the benefits of EBP, only a small percentage consistently use this approach in caring for their patients (Harding et al., ; Melnyk, Fineout‐Overholt et al., ; Melnyk et al., ). In a recent study, Harding and colleagues () found that both clinicians and managers did not view EBP as a core component of clinical care because higher priorities took precedent (e.g., maintaining patient flow).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the literature abounds with studies that indicate this type of practice is far from reality. Findings from research have indicated that, although health professionals from a variety of disciplines believe in the benefits of EBP, only a small percentage consistently use this approach in caring for their patients (Harding et al., ; Melnyk, Fineout‐Overholt et al., ; Melnyk et al., ). In a recent study, Harding and colleagues () found that both clinicians and managers did not view EBP as a core component of clinical care because higher priorities took precedent (e.g., maintaining patient flow).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence is irrefutable: findings from multiple studies indicate that evidence‐based practice (EBP), compared to care that is steeped in tradition, leads to: (a) a higher quality and reliability of health care, (b) improved population health and patient outcomes, including the patient care experience, and (c) reduced costs, now referred to as the Triple Aim in health care in the United States (Fielding & Briss, ; McGinty & Anderson, ; Melnyk, Fineout‐Overholt, Gallagher‐Ford, & Kaplan, ). Despite findings from research supporting the benefits of evidence‐based care and its emphasis in the Affordable Care Act, it is not the standard of practice implemented by many clinicians and healthcare systems across the United States and the globe due to multiple barriers that continue to be a deterrent to the translation of research findings into real‐world practice settings (Fink, Thompson, & Bonnes, ; Harding, Porter, Horne‐Thompson, Donley, & Taylor, ; Melnyk, Fineout‐Overholt et al., ). Among these barriers are: (a) inadequate knowledge and skills in EBP by clinicians, (b) lack of EBP mentors and practice facilitators, (c) misconceptions that EBP takes too much time, (d) cultures and environments that do not support EBP, (e) inadequate resources, and (f) lack of expectations and organizational mandates to implement evidence‐based care (Harding et al., ; Melnyk, Fineout‐Overholt et al., ; Melnyk et al., ; Nagykaldi, Mold, Robinson, Niebauer, & Ford, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, there are possibilities that the influencing factors may change as the implementation goes through. Addressing a single barrier (e.g., low nurse‐to‐patient ratio or knowledge deficit) may not help implement (Harding, Porter, Horne‐Thompson, Donley, & Taylor, ; Jun et al., ). Therefore, a systematic and dynamic perspective is suggested with an ongoing assessment of influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…The department‐wide preparation for the awards involved a strategic and systematic process of: (i) mapping each clinical service area; (ii) collating the best available evidence for each area in the Nutrition Care Process Terminology ‘ADIME’ (assessment, diagnosis, intervention, monitoring and evaluation) format; (iii) identifying and defining evidence‐practice gaps and (iv) prioritising and defining implementation projects from the identified evidence‐practice gaps. This broad, inclusive approach to embedding evidence into practice ensured projects aligned with organisational and departmental priorities to maintain and support staff's engagement and the delivery of an effective and efficient service . The present study describes the service assessment, development, implementation and evaluation undertaken in the department's weight management service.…”
Section: Introductionmentioning
confidence: 99%